The grace of wild things - Fawcett, Heather (Heather M.) (Balzer + Bray, an imprint of HarperCollinsPublishers, 2023)
Fleeing from the orphanage where she lives, Grace makes a deal with the witch in the nearby woods -- if Grace can learn all the witch's spells, she must make Grace her apprentice -- an agreement that leads to an unexpected bond, and an unimaginable sacrifice.